(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the effectiveness of abdominal fluid drainage combined with continuous hemofiltration to treat severe acute pancreatitis with increased abdominal pressure at Nghe An General Friendship Hospital. Subjects: 14 patients diagnosed with severe acute pancreatitis according to Atlanta 2012 criteria, with increased abdominal pressure and were treated with abdominal drainage combined with continuous dialysis at the Intensive Care Department - Friendship Hospital Nghe An General Hospital from January 2023 to September 2023. Methods: Case series study. Results: Grade I increased abdominal pressure: 14.3%; Grade II: 50%; grade II: 21.4%; Grade IV: 14.3%. Continuous dialysis time: Grade I intra-abdominal hypertension: 16.3 ± 2.83 hours; Grade II: 44.5 ± 16.5 hours; Grade III: 46.6 ± 18.7 hours; Grade IV: 82.5 ± 18.3 hours. Average amount of abdominal drainage fluid in the first 3 days: Grade I increased intra-abdominal pressure: 1221.5 ± 451.5 ml; grade II: 1912.12 ± 612.4 ml; grade III: 2978.21 ± 725.7 ml; Grade IV: 3571.21 ± 767.5 ml. The recovered group accounted for 64.3%, abdominal pressure decreased and returned to normal from day 4, average blood pressure tended to gradually increase and remained stable, creatinine decreased rapidly to near normal values after 1 day. week of treatment. Continuous dialysis time ranges from 1-7 days and the number of dialysis filters ranges from 1–8. Conclusion: The cure rate of abdominal fluid drainage combined with continuous hemofiltration to treat severe acute pancreatitis with increased abdominal pressure is 64.3%; Abdominal pressure decreased rapidly, blood creatinine decreased and returned to normal, hemodynamics were stable in the recovery group.